Literature in the Abstract: Althusser and English Studies in England - David Margolies (Studies in 20th & 21st Century Literature, 1994)
Althusser's work arrived just when the disintegrating liberal consensus was shaking the ivory towers of the university. Students protested the war in Vietnam as well as the policies of the university. Althusser offered an understanding of this corrupt world and its distorted self-image. These theories provided an exciting new totalization in which life had meaning and intellectuals, a vital role. In literary studies, students and lecturers assumed that works of literature were anti-scientific, preservers of the status quo, without genuine knowledge. Disillusioned, these students and lecturers condemned Literature as an institution and ignored the individual work. To stop teaching the dominant ideology, they found redemption through abstraction—general principles, abstract structures. Academics found it attractive to raise barricades in the mind, not the street. Althusserian ideas showed lecturers and students that what was thought to be a purely literary or factual matter of aesthetic appreciation was really ideological and political, but the arrogance of the Althusserians, who recognized no theory before Althusser and no value in empirical experience, offended potential allies.
Keywords: Althusser; Marxist philosophy; self-image; corruption; meaning; intellect; academics; mind; aesthetic